Supramolecular hydrogel directed self-assembly of C- and N-doped hollow CuO as high-performance anode materials for Li-ion batteries. Issue 13 (30th January 2017) - Lyu, Fucong; Yu, Sicen; Li, Minchan; Wang, Zhenyu; Nan, Bo; Wu, Shaofei; Cao, Lujie; Sun, Zhifang; Yang, Mingyang; Wang, Wenxi; Shang, Chaoqun; Lu, Zhouguang
Abstract : In situ reduction of Cu 2+ and hydrogel-directed self-assembly into a hollow Cu/Cu2 O nanocomposites with homogeneous C, N doping. Abstract : A novel hollow-structured CuO derived from chitosan-coated Cu/Cu2 O composite hollow spheres was mass produced via a supramolecular hydrogel templating method and homogeneously co-doped with C and N. Evaluation of the as-produced co-doped CuO hollow spheres as anode materials for Li ion batteries showed that they had superior electrochemical properties.